Time for speciation and niche conservatism explain the latitudinal diversity gradient in clupeiform fishes. (31st July 2022) - Egan, Joshua P.; Bloom, Devin D.; Simons, Andrew M.
Abstract: Aim: The latitudinal diversity gradient of increasing species richness from poles to equator is one of the most striking and pervasive spatial patterns of biodiversity. Climate appears to have been key to the formation of the latitudinal diversity gradient, but the processes through which climate shaped species richness remain unclear. We tested predictions of the time for speciation, carrying capacity and diversification rate latitudinal diversity gradient hypotheses in a trans‐marine/freshwater clade of fishes. Location: Global in marine and freshwater environments. Taxon: Clupeiformes (anchovies, herrings, sardines and relatives). Methods: We tested predictions of latitudinal diversity gradient hypotheses using a molecular phylogeny, species distribution data and phylogenetic comparative approaches. To test the time for speciation hypothesis, we conducted ancestral state reconstructions to infer the ages of temperate, subtropical and tropical lineages and frequency of evolutionary transitions between climates. We tested the carry capacity hypothesis by characterizing changes in net diversification rates through time. To test the diversification rate hypothesis, we qualitatively compared the diversification rates of temperate, subtropical and tropical lineages and conducted statistical tests for associations between latitude and diversification rates. Results: We identified four transitions to temperate climates and two transitions out of temperate climates. We found no differences in diversification rates among temperate and tropical clupeiforms. Net diversification rates remained positive in crown Clupeiformes since their origin 150 Ma in both tropical and temperate lineages. Climate niche characters exhibited strong phylogenetic signal. All temperate clupeiform lineages arose <50 Ma, after the Early Eocene Climatic Optimum. Main conclusions: Our results support the time for speciation hypothesis, which proposes that climate niche conservatism and fluctuations in the extent of temperate climates limited the time for species to accumulate in temperate climates, resulting in the latitudinal diversity gradient. We found no support for the carrying capacity or diversification rate hypotheses.